2013
DOI: 10.1590/s1984-29612013000400023
|View full text |Cite
|
Sign up to set email alerts
|

Neospora spp. antibodies in horses from two geographical regions of the state of Santa Catarina, Brazil

Abstract: The aims of this study were to determine occurrences of Neospora spp. IgG antibodies in horses from two geographical regions of the state of Santa Catarina, southern Brazil, and identify risk factors for infection. Analyses were performed on 615 samples using the immunofluorescent antibody test (IFAT ≥ 1:50). Out of the 615 samples, 25 (4.1%) were positive for Neospora spp. The titers for Neospora spp. were distributed as follows: 1:50 (13), 1:100 (eight), 1:200 (three) and 1:400 (one). Out of the 311 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
1
0
8
Order By: Relevance
“…Previous studies have shown the circulation of the agent in different species in the mountainous region of Santa Catarina with occurrence of IgG antibodies against N. caninum in 13.0% of dogs in urban areas of Lages , 21.2% of dogs in rural areas of Lages (MOURA et al, 2012b), 2.6% of horses (MOURA et al, 2013), 4.58% of goats (TOPAZIO et al, 2014) and 5.83% and 7.0% of sheep (DALLA ROSA et al, 2011;MOURA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the circulation of the agent in different species in the mountainous region of Santa Catarina with occurrence of IgG antibodies against N. caninum in 13.0% of dogs in urban areas of Lages , 21.2% of dogs in rural areas of Lages (MOURA et al, 2012b), 2.6% of horses (MOURA et al, 2013), 4.58% of goats (TOPAZIO et al, 2014) and 5.83% and 7.0% of sheep (DALLA ROSA et al, 2011;MOURA et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…nas populações pesquisadas, 14,4% e menos de 5%, respectivamente. Estes estudos tiveram como alvo animais de tração urbanos ou oriundos de áreas rurais, mas ainda assim, indicam que há, nessas condições, contato de equinos com este gênero de protozoários (Villalobos et al 2012, Moura et al 2013.…”
Section: Discussionunclassified
“…Um aspecto que deve ser ressaltado é que o contato de equinos com cães e/ou bovinos é apontado como fator de risco para a infecção por Neospora spp., indicando que a transmissão horizontal também pode ser importante nessa espécie (Moura et al 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Las especies caninum y hughesi son protozoarios intracelulares obligados del género Neospora, pertenece al Phylum Apicomplexa, clase Sporozoea, orden Eucoccidiida, familia Sarcocystidae (4) . La N. caninum en caballos ha sido asociada a abortos y problemas reproductivos (5)(6)(7)(8) , mientras que N. hughesi está relacionada con enfermedades neurológicas (9)(10)(11) , también, asociada con Sarcosystis neuronae, causante de mieloencefalitis protozoaria equina (MPE), identificada como una enfermedad neurológica grave de los caballos, que produce pérdidas significativas en la producción equina, principalmente reportado en Estados Unidos (12) . Los hospederos definitivos de N. caninum identificados son el perro doméstico (13) , coyote (14) , dingo australiano (15) y lobo gris (16) , y como hospederos intermediarios varias especies silvestres y domésticas (17) , sin embargo, los hospederos definitivos de N. hughesi, no se han identificado y el caballo es considerado como único hospedero intermediario potencial (18) .…”
Section: Introductionunclassified